2012
DOI: 10.1111/j.1360-0443.2012.04086.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of routine biochemical validation and an ‘opt out’ referral pathway for smoking cessation in pregnancy

Abstract: AimsTo introduce an 'opt out' referral pathway for smoking cessation in pregnancy and to compare different methods for identifying pregnant smokers in maternity care. Design Pilot study that analysed routine data from maternity and smoking cessation services with biochemical validation of smoking status. Setting Dudley and South Birmingham, England. Participants A total of 3712 women who entered the referral pathway-1498 in Dudley and 2214 in South Birmingham. Measurements Routine monitoring data on smoking at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 12 publications
1
49
0
Order By: Relevance
“…41 For example, NHS Stop Smoking Services (SSSs) in the UK offer behavioural support delivered by trained advisors, in clinic settings, in the home and by telephone, along with access to smoking cessation medications and nicotine replacement therapy (NRT) for smokers motivated to quit. Behavioural support helps pregnant women to stop smoking at least in the short term 42 but only a small minority of women take up the offer of help during pregnancy or after childbirth; the majority of those making quit attempts therefore do so without professional assistance -and most will not succeed. 28 Among those women who do quit during pregnancy, nearly all wish to remain abstinent after the birth of their baby; 43 however, the vast majority relapse within 12 months of the birth.…”
Section: Smoking Cessation In Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…41 For example, NHS Stop Smoking Services (SSSs) in the UK offer behavioural support delivered by trained advisors, in clinic settings, in the home and by telephone, along with access to smoking cessation medications and nicotine replacement therapy (NRT) for smokers motivated to quit. Behavioural support helps pregnant women to stop smoking at least in the short term 42 but only a small minority of women take up the offer of help during pregnancy or after childbirth; the majority of those making quit attempts therefore do so without professional assistance -and most will not succeed. 28 Among those women who do quit during pregnancy, nearly all wish to remain abstinent after the birth of their baby; 43 however, the vast majority relapse within 12 months of the birth.…”
Section: Smoking Cessation In Pregnancymentioning
confidence: 99%
“…This target was to be met by offering a CO breath test to all women at maternity booking. Those whose CO test indicates a level of ≥ 4 parts per million (an appropriate cut-off point identified by members of our research team in a previous study 42 ) or who self-report as smokers are automatically referred to their local smoking cessation service in the area. 42 All women are then contacted by the service and can choose to engage in a face-to-face appointment or to decline support.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If CO measurement was carried out as routinely as measuring blood pressure, the importance of smoking would be underscored and identification of smoking would become routine practice. A comparison of CO with urinary cotinine (a metabolite of nicotine) to identify pregnant smokers [27] found that cotinine was superior and that the CO test was not picking up some women who were smokers. However, given that cotinine has to be sent away to a laboratory for analysis, a routine CO test, using the optimum cut-off of 4 parts per million (p.p.m.…”
Section: Identifying Tobacco Usersmentioning
confidence: 99%
“…The UK National Institute for Health and Care Excellence (NICE) recommends that exhaled CO screening should be used to identify smokers in early pregnancy, and those who do not specifically object should be referred for support; such referrals are known as ‘opt-out’ referrals 18. Evidence for the efficacy of this approach is limited to two studies: an observational audit of Scottish SSS, where the few SSS which were then using CO identification and ‘opt-out’ referrals were noted to have higher referral rates;19 and a ‘before–after’ study that monitored referrals to SSS from two UK hospitals 20. This latter study suggested that, after new referral processes began, referral numbers increased but women's smoking cessation did not; however, no formal statistical testing was used, hindering interpretation of findings 20.…”
Section: Introductionmentioning
confidence: 99%